Perancangan Gambar Objek Wisata Statis Menjadi Dinamis Menggunakan Panorama View Berbasis Web - Suprayogo Nurdiansyah; Fx Wisnu Yudo Untoro (Melek IT : Information Technology Journal, 2015)
Panorama is an image that depicts common view or a widely about parts of any country. Panorama performed part by part on an object. Panorama found in the United Kingdom by Robert Barker in 1787. On the research of this Thesis will be implemented on a static image on tourism, which intends to design static images into a dynamic tourist attractions using the panorama view. Systems that use the built PHP as application interface design and programming languages, and MySQL as its data base. the data used in the form of tour data namely Tugu Pahlawan and the objects that exist in the vicinity. Applications that are built can handle the problem of the existing information on the object static image of the tourist attraction.